2006
DOI: 10.1159/000090880
|View full text |Cite
|
Sign up to set email alerts
|

Valsalva Leak Point Pressure to Determine Internal Sphincter Deficiency in Stress Urinary Incontinence

Abstract: Introduction: Valsalva leak point pressure (VLPP) represents the global competence of the conjunctive forces around the urethra to support increased pressure from the abdominal cavity with transmission to the bladder. Assessment of VLPP has prognostic meaning, but measurement techniques are still subject to controversy. Patients and Methods: One hundred and eight consecutive women with no genital prolapse or bladder hyperactivity exclusively presenting with urinary stress incontinence were submitted to VLPP de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…Kim et al conducted a frequency assessment of select urodynamic signals, and concluded that CLPP and VLPP tests occur with frequency contributions as high as 14 and 7 Hz, respectively. The clinical urodynamic signals collected from the literature for our study show the relevant time to peak pressure as approximately 0.2–0.25 sec (or 4–5 Hz) for CLPPs and 1–2 sec (or 0.5–1 Hz) for VLPPs . This is consistent with the suggestion by Hogan et al that valsalva be defined as lasting more than 2 sec.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Kim et al conducted a frequency assessment of select urodynamic signals, and concluded that CLPP and VLPP tests occur with frequency contributions as high as 14 and 7 Hz, respectively. The clinical urodynamic signals collected from the literature for our study show the relevant time to peak pressure as approximately 0.2–0.25 sec (or 4–5 Hz) for CLPPs and 1–2 sec (or 0.5–1 Hz) for VLPPs . This is consistent with the suggestion by Hogan et al that valsalva be defined as lasting more than 2 sec.…”
Section: Discussionsupporting
confidence: 91%
“…The CLPP signals obtained from literature have time to peak pressure 0.2–0.25 sec, while the VLPP signals have time to peak pressure 1–2 sec . Thus, VLPPs are in the range of slowly changing signals in which ACCs measured peak pressures similar to those measured simultaneously by WFCs.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The maximum urethral closure pressure (MUCP) and the Valsalva leak point pressure (VLPP) were used separately and in combination as parameters to study urethral integrity and as outcome predictors in patients who underwent mid-urethral sling operations for SUI [4,5] . At a 3-month follow-up, Miller et al [6] found that TOT was nearly 6 times more likely to fail than TVT when subjects had a preoperative MUCP at or below 42 cm H 2 O.…”
Section: Introductionmentioning
confidence: 99%